EFFECTS OF DRUGS IN OPTIMIZING BLOOD PRESSURE AND CARDIAC OUTPUT - SRINIVAS TEJA B,; KRISHNA SAI V,; RAGHU RAM V,; Rao Nadendla, Rama (Asian Journal of Pharmaceutical and Clinical Research, 2015)
In the cardiovascular system the drugs effects the conditions like Â Peripheral vascular tone ,Inotropic state of the heart ,Chronotropic state of the heart Clinically these drugs are used in ,Acute ischemic heart disease,Acute and chronic heart failure,Shock (especially cardiogenic),Cardiac arrest. when the drugs that are used during the cardiac treatment may give positive results when given in the correct dosage and gives negative results if there is slight variation in the dose and its frequency. Keywords: significant effects, cardiac arrest, dose adjustment.